1996
DOI: 10.1046/j.1523-1739.1996.10051366.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Riparian Buffer Strips as Movement Corridors by Forest Birds

Abstract: We conducted a 3‐year field experiment to measure the frequency of bird movements through riparian buffer strips before and after harvesting of adjacent forest. Our study was conducted in the boreal mixed wood forest of Alberta and was designed to determine empirically whether songbirds use riparian buffer strips of forest connecting forest reserves as corridors and if they move along these buffer strips more frequently than they cross adjacent clearcuts. We used mist nets to obtain an index of the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
149
1
9

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(164 citation statements)
references
References 0 publications
5
149
1
9
Order By: Relevance
“…Gaps in forest cover may generally be perceived as inhospitable by forest birds (19,24,25), because they are more detectable by predators there (26). Other studies have suggested that forest birds avoid gaps over a certain threshold of size (19,27), but no previous corridor study has provided enough spatial resolution to assess cumulative gap crossing behavior at a landscape scale.…”
Section: Discussionmentioning
confidence: 99%
“…Gaps in forest cover may generally be perceived as inhospitable by forest birds (19,24,25), because they are more detectable by predators there (26). Other studies have suggested that forest birds avoid gaps over a certain threshold of size (19,27), but no previous corridor study has provided enough spatial resolution to assess cumulative gap crossing behavior at a landscape scale.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that streams may act as movement corridors for forest birds (Machtans et al 1996). The general value of corridors for dispersal has been questioned (Machtans et al 1996;Simberloff and Cox 1987;Gustafsson and Hansson 1987;Niemelä 2001;Ö ckinger and Smith 2008). Several factors may influence the general value of corridors.…”
Section: Forest Generalist Speciesmentioning
confidence: 96%
“…As ecotones located at the intersection of land and water, riparian zones are exceptionally rich in biodiversity (Naiman and Décamps, 1990;Naiman et al, 1993). They represent ecological corridors (Rodriguez-Iturbe et al, 2009) and provide a crucial habitat for terrestrial animals and for migrating birds (Hilty and Merenlender, 2004;Machtans et al, 1996;Skagen et al, 1998Skagen et al, , 2005. The width of a zone can range from a few metres to several kilometres.…”
Section: Introductionmentioning
confidence: 99%